What determines public expenditure allocations? A review of theories, and implications for agricultural public investments - Mogues, Tewodaj (International Food Policy Research Institute, 2012)
This paper addresses the determinants of public expenditure policies, by reviewing theories and empirical investigations of what features explain the budget process and how the various attributes of actors—including politicians, bureaucrats, interest groups, and donors—and of institutions and political and economic governance environments affect the prioritization of public investments. It draws conclusions with regard to the determinants of agricultural public investments.